The Importance of Multicultural Education in Indonesia - Ikhsan, MT Hartono; Giwangsa, Sandi Fauzi (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
Indonesia is a multicultural country both ethnic, religion, cultural, regional languages from Sabang to Merauke. This diversity on one hand is a gift for Indonesian people but if it is not addressed wisely, this difference has the potential to be a source of conflict for this nation. Multicultural education becomes a necessity so that people do not only know about the existed diversity but also must be practical and positive towards diversity. Therefore, this multicultural education should be instilled as early as possible in the next generation of our nation in order to maintain the unity of this nation amid the differences that exist.